Dual Monoclonal Antibody Therapy for a Severe Asthma Patient - Domingo, Christian; Pomares, Xavier; Morón, Anisi; Sogo, Ana (Frontiers in Pharmacology, 2020)
Introduction Omalizumab, the first biological treatment for severe allergic bronchial asthma, has been on the market for more than a decade. Omalizumab was initially considered to be an IgE-blocking agent, and therefore, an inhibitor of the Th2 (allergic or adaptive) cascade. More recently, other monoclonal antibodies for severe eosinophilic asthma have become available, which exert an anti-eosinophilic effect basically by blocking IL5 or its receptor. These agents exert this effect regardless of the origin of the eosinophils (i.e., the adaptive or the innate immune system). Case study An oral corticosteroid-dependent allergic asthma patient was treated with omalizumab. After a year of treatment, the improvement remained very limited and the medical team proposed discontinuation. However, the patient felt that her asthma had improved and she refused to give up the therapy, which continued for ten years. The mean accumulated oral corticosteroid dose per month during the last year was around 200 mg; despite this, the FEV1 was low, Since the patient had a high number of eosinophils in peripheral blood, she accepted a switch to mepolizumab when this agent became available. One year later, the clinical improvement was limited and severe symptoms of allergy reappeared, and a combination of monoclonal antiobodies (omalizumab and mepolizumab) was proposed. Results After 24 months of dual therapy, a marked improvement in the FEV1 was observed, reaching the normal range, and the OC dose was reduced to 2.5 mg per day of prednisolone. No side effects were observed. Conclusions In some severe allergic asthma patients with persistently high eosinophil counts in peripheral blood and who are considered non- or mild responders to anti-IgE and anti-IL5 administered individually, a combination of the two antibodies covering the entire T2 spectrum may be effective.